Atrial Tachycardias Arising from Ablation of Atrial Fibrillation: A Proarrhythmic Bump or an Antiarrhythmic Turn?. (7th April 2010) - Shah, Ashok J.; Jadidi, Amir; Liu, Xingpeng; Miyazaki, Shinsuke; Forclaz, Andrei; Nault, Isabelle; Rivard, Lena; Linton, Nick; Xhaet, Olivier; Derval, Nicolas; Sacher, Frederic; Bordachar, Pierre; et al.
Abstract : The occurrence of atrial tachycardias (AT) is a direct function of the volume of atrial tissue ablated in the patients with atrial fibrillation (AF). Thus, the incidence of AT is highest in persistent AF patients undergoing stepwise ablation using the strategic combination of pulmonary vein isolation, electrogram based ablation and left atrial linear ablation. Using deductive mapping strategy, AT can be divided into three clinical categories viz. the macroreentry, the focal and the newly described localized reentry all of which are amenable to catheter ablation with success rate of 95%. Perimitral, roof dependent and cavotricuspid isthmus dependent AT involve large reentrant circuits which can be successfully ablated at the left mitral isthmus, left atrial roof and tricuspid isthmus respectively. Complete bidirectional block across the sites of linear ablation is a necessary endpoint. Focal and localized reentrant AT commonly originate from but are not limited to the septum, posteroinferior left atrium, venous ostia, base of the left atrial appendage and left mitral isthmus and they respond quickly to focal ablation. AT not only represents ablation-induced proarrhythmia but also forms a bridge between AF and sinus rhythm in longstanding AF patients treated successfully with catheter ablation.